2021
DOI: 10.3389/fpsyt.2021.653642
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Measures in At-Risk Mental State and Early Stages of Schizophrenia: A Systematic Review

Abstract: Introduction: Electrophysiological (EEG) abnormalities in subjects with schizophrenia have been largely reported. In the last decades, research has shifted to the identification of electrophysiological alterations in the prodromal and early phases of the disorder, focusing on the prediction of clinical and functional outcome. The identification of neuronal aberrations in subjects with a first episode of psychosis (FEP) and in those at ultra high-risk (UHR) or clinical high-risk (CHR) to develop a psychosis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 253 publications
(578 reference statements)
3
40
0
Order By: Relevance
“…These results expanded a previous finding in chronic schizophrenia with a short clinical follow-up (6 months) ( 11 ) and further supported a clinical utility of dMMN at earlier illness stages as a predictive marker of treatment response and recovery. Given that CHR individuals likely have reduced dMMN amplitudes, which may underpin their psychosis risk ( 12 , 13 ) and functional and symptomatic improvement at follow-up period ( 22 , 27 ), dMMN abnormalities may be a rather stable biomarker during the course of psychosis that could not be explained only by the effect of antipsychotic medication and/or illness chronicity after the onset. It is considered that MMN is generated by a fronto-temporal network associated with pre-attentive sensory processing ( 16 ) and that MMN reduction in schizophrenia may reflect N-methyl-D-aspartate (NMDA) receptor hypofunction ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results expanded a previous finding in chronic schizophrenia with a short clinical follow-up (6 months) ( 11 ) and further supported a clinical utility of dMMN at earlier illness stages as a predictive marker of treatment response and recovery. Given that CHR individuals likely have reduced dMMN amplitudes, which may underpin their psychosis risk ( 12 , 13 ) and functional and symptomatic improvement at follow-up period ( 22 , 27 ), dMMN abnormalities may be a rather stable biomarker during the course of psychosis that could not be explained only by the effect of antipsychotic medication and/or illness chronicity after the onset. It is considered that MMN is generated by a fronto-temporal network associated with pre-attentive sensory processing ( 16 ) and that MMN reduction in schizophrenia may reflect N-methyl-D-aspartate (NMDA) receptor hypofunction ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fMMN amplitude at baseline was mildly decreased in the FES group compared to the H group, but there was no difference between the R and NR groups. This result may be partly explained by the notion that fMMN has less stability and replicability than dMMN ( 50 ), but it is also possible that fMMN abnormalities in schizophrenia emerge more robustly only during the chronic stages ( 12 ). Indeed, several fMMN studies in schizophrenia have demonstrated that its amplitude is associated with illness duration ( 51 ) and longitudinally declines during early illness stages ( 30 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In psychiatric research, P300 started to gain attention due to the consistent alterations recorded in subjects with schizophrenia. In fact, numerous studies have reported a reduction in P300 amplitude and delayed latency of its peak both in subjects with chronic schizophrenia [ 95 , 96 , 97 ] and in subjects at prodromal and early stages of the illness [ 98 ].…”
Section: Introductionmentioning
confidence: 99%